Determinants of tenants’ satisfaction at Pasaraya Komuniti @Mart Kempas, Johor Bahru / Muhamad Efendy Jamhar - Jamhar, Muhamad Efendy (Faculty of Business Management, 2017)
The purpose of this research is to identify the most significant variable to measure the determinants of tenants’ satisfaction at Pasaraya Komuniti @Mart Kempas, Johor Bahru. There are four independent variables to measure tenants’ satisfaction which are ambience, service performance, facilities and service quality. The research is being conducted towards tenants at Pasaraya Komuniti @Mart Kempas. The information is gathered by distribution of questionnaire to the tenants by using simple random sampling. Out of 130 tenants at Pasaraya Komuniti @Mart Kempas, only 97 questionnaires distributed and answered by the respondents. The feedbacks on the answeried questionnaires was analyzed and summarized by using the Statistical Package for Social Science (SPSS). Statistical analysis such as frequency analysis, reliability analysis, correlation analysis and multiple regressions were used. The results of the research shows that out of four independent variables, only three of the variables which are ambience, service performance and service quality are the significant while facilities are not significant towards tenant satisfaction at Pasaraya Komuniti @Mart Kempas. The findings of this study may contribute to strategic planning of the building. Several suggestions for future research are also presented in this study.